KIMA — A Holographic Telepresence Environment Based on Cymatic Principles - Gingrich, Oliver; Renaud, Alain; Emets, Eugenia (Leonardo (Oxford), 2013)
KIMA is a holographic surround-sound installation that visualizes telepresence as both a phonetic and a synaesthetic phenomenon. The performance piece is based on the physical conditions of cymatics—the study of physically visible sound wave patterns. Two environments, a quad surround and a holographic interface, build the framework of a telematic experience that illustrates communication as wave forms while focusing on the relationship between sound and matter.